FRI0519 A Cross-Cultural Validation of the Simple Measure of Impact of Lupus Erythematosus in Youngsters (Smiley) Among Filipino Pediatric Lupus Patients. (9th June 2015) - Punzalan, J.; Bernal, C.; Canonigo, B.; Cabansag, M.R.; Flores, D.; Galutira, P.J.; Chan, R.
Abstract : Background: Systemic lupus erythematosus (SLE) is one of the most common autoimmune disorders predominates in women of childbearing age. Children and adolescents represent 15-20% of all patients with SLE. Children systemic lupus erythematosus patients have more severe symptoms at the onset. Renal involvement occurs in 50-75% of all children SLE patients, mostly within the first 2 years after diagnosis. Simple Measure of Impact of Lupus Erythematosus in Youngsters (SMILEY) is the only health specific quality of life tool for pediatric SLE, which has been translated to different languages except in Filipino. Objectives: The primary objective of this study was to develop a Filipino translation of the SMILEY and to examine the validity and reliability of this translation. Methods: The SMILEY was translated into Filipino by a bilingual individual and back-translated by another bilingual individual blinded from the original English version. The translation was evaluated for face and content validity by a panel of experts and subjected to pilot testing. The pilot-tested translation was used in the validity and reliability testing proper. The SMILEY, together with the previously validated PEDSQL 4.0 Generic Core Scale was administered to lupus pediatric patients and their parent at two separate occasions: a baseline and a re-test seven to fourteen days apart. Tests for convergent validity, internal consistency, and test-retest reliability were performed. Results: A total of fifty children and their parent were recruited. The mean age was 15.38±2.62 years, mean education at high school level. The mean duration of SLE was 28 months. Currently, all subjects were receiving or had previously received steroids. Most common immunomodulating drug used was cyclophosphamide (56%), followed by mycophenolate mofetil (14%) and azathioprine (4%). Most of the parents that participated were mothers. Most of the subjects were from the national capital region (52%) were Filipino language is widely used. Subjects found the questionnaires to be relevant, easy to understand and answer. The validity of the SMILEY was demonstrated in terms of content validity, convergent validity, internal consistency, and test-retest reliability. Age, socioeconomic status and educational attainment did not show significant effect on the scores. The difference between scores of child and parent report were showed to be significant with SMILEY total ( p=0.0214 ), effect on social life ( p=0.0000 ), and PEDSQL physical function ( p=0.0460 ). Child reports showed higher scores for the following domains compared to their parent reports. Conclusions: SMILEY is a brief, easy to understand, valid and reliable tool for assessing pediatric SLE specific HRQOL. It will be useful in providing better care, understanding and may offer critical information regarding the effect of SLE in the quality of life of our pediatric lupus patients. It will help physician understands the needs of their patient not only on treatment of the specific disease but as well as the impact of the treatment on their daily lives. References: Moorthy, LN, Peterson, et al. Quality of Life in Children with Systemic Lupus Erythematosus. Current Rheumatology Rep. 2005; 7:447-452 Disclosure of Interest: None declared